PENGEMBANGAN MEDIA KARTU CHEMO-EDUTAINMENT UNTUK PEMBELAJARAN TATANAMA SENYAWA KIMIA SEBAGAI UPAYA MENINGKATKAN AKTIFITAS BELAJAR SISWA (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract Development research has been done to produce learning media based Chemo-edutainment to learning nomenclature of chemical compounds and to know the quality of learning media that is developed. Media cards that are developed adopting the game of dominoes card.Consists of 28 pieces of cards peer packaged. Each card is divided into two parts, that are the part that was written the name of the compound and the part that was written chemical formula. So in a card package contains 28 names of compounds and 28 chemical formula that are accordance with the rules oft he IUPA Cnomenclature.To using that the name of the compound and the chemical formula matched as the suitability of mate cards. Expected this learning media that is developed will be able to improve student learning activities, and will impact on learning outcome. Based on assessment from 2 validator by 3 assessment that are format, content and technical. The average result is 4.40 with a decent categories used. As a follow up will be applied by classroom action research to look at the impact of media cards that have been developed for the activity and student learning outcome.Keywords :learning media, Chemo-edutainment , chemical formula